(untitled) (International relations and international law Journal, 2018)
An analysis ofthe constitutionsof differentcountries shows thatany one of them, as the Fundamental Law ofthe State andtakinga main place in the hierarchyof nationalsources of law, may have a differentform, content, features and functionsin accordancewith national traditionsornature ofthe form of government, the structure of the stateandthe currentpolitical regime.The definitions ofthe essence ofthe constitutioncan’t be identicalwith definitions ofthe concept ofconstitution. The category of «the essence of the constitution»,because of itssocio-political content is multi-dimensionalcategoryand it hasdifferent aspects andrequires consideration ofa variety ofdomesticandinternational approaches. Key words: constitution, the Fundamental Law, the essence of the Constitution, theprinciples, direct actions of law, rights, freedoms, responsibilities, citizens, law abiding state, stateauthorities.